2020
DOI: 10.1109/access.2020.2991688
|View full text |Cite
|
Sign up to set email alerts
|

Truly Generalizable Radiograph Segmentation With Conditional Domain Adaptation

Abstract: Digitization techniques for biomedical images yield disparate visual patterns in radiological exams. These pattern differences, which can be viewed as a domain-shift problem, may hamper the use of data-driven approaches for inference over these images, such as Deep Neural Networks. Another noticeable difficulty in this field is the lack of labeled data, even though in many cases there is an abundance of unlabeled data available. Therefore, an important step in improving the generalization capabilities of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
(99 reference statements)
0
9
0
Order By: Relevance
“…They employed a Mask R-CNN (He et al, 2017) trained over binary masks that separated the teeth from the background and showed that their approach outperformed traditional solutions to the task. The authors also made their data public under the name UFBA-UESC Dental Image Data Set 3 , which proved to be a valuable resource as it has been extensively used by many works (Koch et al, 2019;Zhao et al, 2020;Oliveira et al;Chen et al, 2021;Cui et al, 2021;Hsu and Wang, 2021). In an extension of Silva et al's work, Jader et al (2018) segmented tooth instances on radiographs of the UFBA-UESC Dental Image Data Set also using Mask R-CNN, though not numbering them.…”
Section: Imaging In Dentistrymentioning
confidence: 99%
“…They employed a Mask R-CNN (He et al, 2017) trained over binary masks that separated the teeth from the background and showed that their approach outperformed traditional solutions to the task. The authors also made their data public under the name UFBA-UESC Dental Image Data Set 3 , which proved to be a valuable resource as it has been extensively used by many works (Koch et al, 2019;Zhao et al, 2020;Oliveira et al;Chen et al, 2021;Cui et al, 2021;Hsu and Wang, 2021). In an extension of Silva et al's work, Jader et al (2018) segmented tooth instances on radiographs of the UFBA-UESC Dental Image Data Set also using Mask R-CNN, though not numbering them.…”
Section: Imaging In Dentistrymentioning
confidence: 99%
“…Moreover, domain adaptation could adapt domain shifts in appearance and semantic levels of an object to achieve higher accuracy and effectiveness [24][25]. Hugo et al [26] proposed a new method of domain adaptation named the Conditional Domain Adaptation Generative Adversarial Network (CoDAGAN) for segmentation purposes in biomedical images. It merges unsupervised [27] and supervised networks to become a semisupervised method that can learn from unlabeled and labeled data.…”
Section: B Domain Adaptationmentioning
confidence: 99%
“…Cycle‐GAN 37 and its variants are frequently integrated into domain adaptation methods to address the domain shift. Oliveira et al 38 . proposed the adversarial‐networks based domain adaptation method to learn from both labeled and unlabeled data.…”
Section: Related Workmentioning
confidence: 99%